Cytological Studies of Some Woody Species - Khosia, P. K.; Kaur, Inderjit (Indian Forester, 1974)
Melotic studies of 20 species belonging to 13 genera in 7 families had been undertaken. Terminalla arjuna Bedd. is a lone case of melotic study which revealed relatively large sized chromosomes in contrast to vast majority of angiosperms. Melotic course is normal among all the taxa under review. Possibility of the improvement of timber species through induced ploidy is also discussed.